Effectiveness of head-mounted air supply in reducing pollutant exposure: A static case. (15th April 2023) - Wei, Xiaobin; Xu, Yukun; Yu, Yanlei; Ma, Mingyao; Niu, Guozhen; Cao, Guangyu; Wang, Lan; Gao, Jun
Abstract: This study presents a head-mounted air supply for reducing pollutant exposure during industrial activities. The optimization of the air outlet, the effectiveness of different flow rates, and the effects of the human body's microenvironment were explored in detail while using the ventilated helmet under static condition, i.e., without human movement. Results showed that fresh air passing through the helmet formed an airflow barrier in front of the wearer's face that effectively prevented pollutants from entering the breathing zone. The air outlet of the helmet should be optimized by increasing the opening angle, reducing the distance to the forehead, and increasing the width. The following relatively optimal parameters were selected: an opening angle of 180°, a distance of 10 mm, and a width of 32 mm. On the basis of comparisons at flow rates of 2–20 L/s, 8 L/s was considered the most effective, with the reduction in pollutant exposure reaching 98.8%. Moreover, at a flow rate of 8–10 L/s, ventilation effectiveness could remain stable at different inhalation volumes (6–30 L/min). The human body's thermal plume can interfere with personalized air and reduce the effectiveness. This study provides a new and improved method for workers' ventilation and respiratory protection during industrial production. Highlights: A head-mounted air supply considering an actual terminal structure is proposed. Effectiveness of inhalation exposure reduction can reach 98.8% at 8L/s. There is a flow rate range that is rarely affected by inhalation volume increase. Human thermal plume increases inhalation exposure of pollutant. Protection for ocular surface against pollutant exposure is evaluated.